2022
DOI: 10.3390/ijerph19042294
|View full text |Cite
|
Sign up to set email alerts
|

Adenomyosis as a Risk Factor for Myometrial or Endometrial Neoplasms—Review

Abstract: Adenomyosis is a common benign gynecological condition, defined as an extension of endometrial tissue into the myometrium. Some studies suggest that adenomyosis could be a favorable prediction factor associated with survival outcomes in endometrial cancer. The aim of our systematic review was to investigate the current knowledge regarding adenomyosis and a possible molecular mechanism of carcinogenesis in adenomyotic lesions. In addition, the long-term prognosis for patients with endometrial cancer and coexist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…Some studies have even claimed that these conditions are related, but they have not shown consistent results nor reached an accurate conclusion yet. [ 33 , 34 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have even claimed that these conditions are related, but they have not shown consistent results nor reached an accurate conclusion yet. [ 33 , 34 ]…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have even claimed that these conditions are related, but they have not shown consistent results nor reached an accurate conclusion yet. [33,34] The association between adenomyosis and other diseases still requires extensive clinical and molecular investigation. However, in any situation, the presence of adenomyosis does not exclude the possibility of comorbid diseases, so if there are symptoms such as abnormal uterine bleeding, efforts should be made to initially exclude adenomyosis as the primary cause.…”
Section: Discussionmentioning
confidence: 99%
“…Szubert et al in the review of adenomyosis as a risk factor for myometrial or endometrial neoplasms concluded that adenomyosis may be a potential risk factor for myometrial or endometrial neoplasms [15].…”
Section: Discussionmentioning
confidence: 99%
“…Different from endometrium adenocarcinoma in stage IB, which invades into deep myometrium from the eutopic endometrium, EAAFA arises from the adenomyotic epithelium within deep myometrium without invasion to surrounding tissues. However, further accumulation of the cases and molecular investigation are needed (17).…”
Section: Treatment and Prognosismentioning
confidence: 99%